PRODUKSI CITRA POLISI DALAM FILM : SEBUAH UPAYA SAKRALISASI (Analisis Genre Pemenang Police Movie Festival 2017-2019) - Sokowati, Muria Endah; Nurnisya, Frizki Yulianti (Interaksi: Jurnal Ilmu Komunikasi, 2021)
The image of the police is understood in various ways. In the news, the police are often presented with a negative image. However, there is a tendency for the police to be sanctified as saints in the film. This article attempts to explain the forms of sacralization of police images displayed in cinema. Uses genre analysis to answer the re-search questions. The Police Movie Festival in 2017-2019 was the chosen research object since the Indonesian National Police organize this film festival, it will be seen how they want to be shown in the film. As a result, the Police Movie Festival winners increasingly sanctify the police's image as heroes, patriotic, humanist, and a tolerant and pluralist figure. These images that emerge can obscure that the police also often justify violence when dealing with civilians who are supposed to be the parties they protect.